2011
DOI: 10.1016/j.jnutbio.2010.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of high glucose-induced proinflammatory cytokine production in monocytes by curcumin

Abstract: Diabetes is a pro-inflammatory state. We have previously shown increased monocyte proinflammatory cytokines in patients with Type 1 and Type 2 diabetes. High glucose induces proinflammatory cytokines via epigenetic changes. Curcumin, a polyphenol responsible for the yellow color of the spice turmeric, is known to exert potent anti-inflammatory activity in vitro. Recent studies indicate that it may regulate chromatin remodeling by inhibiting histone acetylation. In this study, we aimed to test the effect of cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 55 publications
(53 reference statements)
4
121
0
1
Order By: Relevance
“…Curcumin inhibited p300-mediated acetylation of RelA, an isoform of NF-jB, which attenuated interaction with IjBa, leading to decreased IjBa-dependent nuclear export of the complex through a chromosomal region maintenance-1-dependent pathway (Chen et al 2001). In the same way, Yun et al (2010) found that curcumin treatment significantly reduced HAT activity, p300 levels, and acetylated CBP/p300 gene expression and consequently suppressed NF-jB binding. Thus, curcumin's ability to suppress p300/CBP HAT activity may be responsible, at least in part, for its potent NF-jB inhibitory activity.…”
Section: Effect Of Curcumin On Histone Acetylation/deacetylationmentioning
confidence: 65%
“…Curcumin inhibited p300-mediated acetylation of RelA, an isoform of NF-jB, which attenuated interaction with IjBa, leading to decreased IjBa-dependent nuclear export of the complex through a chromosomal region maintenance-1-dependent pathway (Chen et al 2001). In the same way, Yun et al (2010) found that curcumin treatment significantly reduced HAT activity, p300 levels, and acetylated CBP/p300 gene expression and consequently suppressed NF-jB binding. Thus, curcumin's ability to suppress p300/CBP HAT activity may be responsible, at least in part, for its potent NF-jB inhibitory activity.…”
Section: Effect Of Curcumin On Histone Acetylation/deacetylationmentioning
confidence: 65%
“…Curcumin could ameliorate glucose metabolism, and could also prevent diabetic complications by increasing HDAC-2 and decreasing p300-HAT in human monocytes with a consequent reduction of NFkB signaling and vascular inflammation. 83 In Table 2, we report a completed and published clinical trial (NCT01029327) demonstrating that curcumin increases postprandial serum insulin levels without affecting plasma glucose levels in healthy subjects. 84 Additionally, another completed and published clinical trial (NCT01646047) studied the effects of a novel multi-component dietary supplement (vitamins, turmeric root extract, and so on) on the visual function and retinal structure of diabetic patients with and without early diabetic retinopathy.…”
Section: Histone Acetyltransferase Inhibitorsmentioning
confidence: 99%
“…However, although curcumin is able to modulate histone deacetylases and acetyltransferases, DNA methyltransferase I, and miRNAs (Reuter et al, 2011), until now no studies have analyzed the involvement of curcumininduced epigenetic mechanisms in obesity models. An interesting precedent is the study of Yun et al, (Yun et al, 2011), in which curcumin decreased hyperglycemia-induced cytokine production in monocytes via epigenetic changes involving NFκB, including a decrease of HAT activity, p300 level and acetylated CBP/p300 gene expression, and the activation of HDAC2.…”
Section: Polyphenols and Other Plant Compoundsmentioning
confidence: 99%